In vivo anti-Toxoplasma activity of aripiprazole - Saraei, Mehrzad (Iran J Basic Med Sci, 2015)
OBJECTIVE(S): There are supportive evidences about the possible role of latent Toxoplasma. gondii infections on the behavior and neurologic functions, such as increased dopamine levels in the brain. The aim of this study was to examine anti-toxoplasma activity of aripiprazole that is an atypical anti-psychotic drug in mice. MATERIALS AND METHODS: Mice were randomly divided into four groups, including; control, vehicle, aripiprazole 10 mg/kg, and aripiprazole 20 mg/kg. The mice were inoculated intraperitoneally with mice brain suspension containing tissue cysts. At the end of second month, the number of cysts was counted in smears prepared from brain homogenate by optical microscope. RESULTS: There was no significant difference between mean logarithms of brain cyst numbers of aripiprazole groups compared with control. CONCLUSION: Results indicate that in aripiprazole groups, the brain cystogenesis was not decrease. Further study needs to investigate the role of anti-psychotic drugs on T. gondii.